2019
DOI: 10.1080/09687637.2018.1555231
|View full text |Cite
|
Sign up to set email alerts
|

Developing expertise, customising sleep, enhancing study practices: exploring the legitimisation of modafinil use within the accounts of UK undergraduate students

Abstract: Introduction and aim: Increasing numbers of students are reportedly using prescription medications to enhance cognition. This study aimed to generate qualitative data on UK students’ understandings and perspectives of the risks and benefits surrounding so-called ‘study drugs’ (particularly, modafinil). Design and methods: Fifteen undergraduate students studying biomedical science subjects were interviewed about their perspectives on study drugs. Interviews were recorded and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…A 2019 UK qualitative study with Biomedical Science undergraduate students examined their understanding of the risks of non-prescribed drugs, and particularly modafinil, misuse. Drivers of use were related to university pressures and desires to increase productivity; the customisation of the sleep–wake cycle was described as a key benefit of ‘study drug’ use [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2019 UK qualitative study with Biomedical Science undergraduate students examined their understanding of the risks of non-prescribed drugs, and particularly modafinil, misuse. Drivers of use were related to university pressures and desires to increase productivity; the customisation of the sleep–wake cycle was described as a key benefit of ‘study drug’ use [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Steward and Pickersgill (2019) found that all their CE users had ingested modafinil, with only some also having tried methylphenidate and amphetamine salt mixtures for the purpose of study. In fact, students described how the use of methylphenidate and amphetamine salt mixtures could result in dependence and hence these were approached more cautiously [ 32 ]. Overall, however, the use of methylphenidate has significantly increased, with its consumption, in defined daily doses, having increased to approximately 2.4 billion worldwide [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, recent studies of PCED users have found that their moral evaluations of PCED use continually shift within the same social context as social and time pressures rise and fall (Krøll, 2019;Steward & Pickersgill, 2019, both this issue). For example, it is well established in the literature that students tend to use PCEDs at times of increased pressure (e.g.…”
Section: Moralising Justifying and (De)legitimating Pcementioning
confidence: 99%
“…There is then, a need for scholars to look beyond the 'West' and take a more global and comparative perspective to examine understandings of PCE and PCED consumption practices in varied socio-cultural and regulatory environments. Because PCDE use has often been connected to the pressure and stress in western educational institutions and workplaces (Bjønness, 2019, Steward & Pickersgill, 2019Krøll, 2019;Maier et al, 2018;Sattler, 2019), comparative work, analysing different settings and contexts, would help us gain a more nuanced knowledge about the phenomenon. We might also think of future work around pharmaceutical production and 'global supply chains' and how these act to shape consumption practices, to uncover and connect the production and manufacture of pharmaceuticalswhich often takes places within developing countrieswith their distribution, sale and use (Gabe et al, 2015).…”
Section: Summary and Future Agendasmentioning
confidence: 99%
“…Though as noted in Steward and Pickersgill (2019) care should be taken if and when university institutions decide on CE drug use policy.…”
Section: Institutional Positionmentioning
confidence: 99%